Młody prekariat, czyli codzienna niepewność - Majerek, Bożena (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Non-standard and flexible forms of employment have caused the precariat class to emerge. According to the statistics, young people are the core of this group. Their everyday lives lack basic sense of security, which forces them to live in constant threat and uncertainty. It seems that those negative experiences result in delaying, postponing or hindering the whole process of realizing their developmental tasks. At the same time all the attempts that young adults make to deal with precariat reality generate new social phenomena, such as the emergence of „boomerang kids”.
Keywords: boomerang kids; precariat; uncertainty; young adult